A Monograph of the Genus Ulota s.l. (Orthotrichaceae, Moss) - WANG, Qing-Hua (EDP Sciences, 2023)
Mosses are one of the most ancient terrestrial plants. Their small size and rich species have increased the difficulty in classification and thus there are still many taxonomic issues to be solved. The moss genus Ulota provides a good example in this regard. Engaged in the world taxonomic revision of this epiphytic moss for many years, the authors present the main conclusions of their research in this book. It not only introduces the taxonomy, phylogeny and evolution of Ulota, but also provides detailed and comprehensive information on the 50 species confirmed in this study, illustrated and accompanied by beautiful color photos, SEM images and distribution maps. This book brings together the latest findings of Ulota and useful reference for species classification for professionals and amateurs
Description based on online resource; title from PDF title page (publisher's Web site, viewed 01. Nov 2023)
Keywords: SCIENCE / Life Sciences / Botany